THE STAGES OF THE DEVELOPMENT OF BC SPORTS AND THEIR IMPACT ON SOCIETY (STUDY AND ANALYSIS) - Hassan, Mohamed Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Historians have focused on economic and political history. They recounted the lives of kings and queens, that of prime ministers and presidents. They have often neglected social history. We believe that history should not be limited to economic and political aspects; it should also be interested in artistic and educational events; she should describe how social activities evolve. Social history should teach us how people lived, how they loved and how they played. The history of sport is an essential aspect of social history. It deals with the particular aspects of human activities, namely sports and games. If we stop thinking, we realize that people spend a lot of their time in sports; by reading sports pages; either by acting as a spectator or participant. Sport occupies an important place in the life of the nation. It reflects the socio-cultural system that allows it to exist. In recent years, the history of sport has become an academically respectable area. Specialists have been trained in various departments of physical education, human movement studies and human kinetics. These specialists have learned to master the historical method. They gained an understanding of the importance of the history of sport in the field of social history. There are now international associations in sports history, a North American association, a Canadian association. In addition, researchers can publish the results of their research in journals entirely devoted to this field. These specialists gradually reveal the role played by sports and games in various societies and civilizations. The following countries have contributed most to the advancement of the history of sport: Germany, the United States, Australia and Canada. If we make an exception for the German language, most of the work in sport history has been published in English. Few French Canadians have been interested in this area, although Francophones have made a significant contribution to the world of sport. They have been noticed in tennis, hunting, dancing, sailing, gymnastics, cycling and fencing. It is also a Frenchman who has contributed the most to the development of the Olympic Games of the twentieth century, Baron Pierre de Coubertin. Many Canadian sports originate in Quebec. These include: snowshoeing, sliding, ice hockey, fencing, weightlifting, curling, lacrosse, billiards, cycling, tennis, gymnastics, boating, swimming, etc. Research on these activities and the traditional games of French Canadians have been sporadic. Some researchers like Yvan Leduc, Donald Guay, Claude Lessard and Jean-Paul Massicotte have drawn from the sources. However, we are entering a new era that will recognize the contribution of Francophone researchers to the world of sport.